Characteristics of anorectal malformations - Masitha, Masitha; Haidir Bima; Akhmad Kadir (Sean Institute, 2024)
Anorectal malformation is a congenital abnormality that shows a condition without an anus or with an imperfect anus. Anorectal malformation is a common congenital problem that occurs in 1 in 5,000 births. Anorectal malformation is a classification where anorectal malformations are divided into high and low locations, as well as whether or not a colostomy is necessary. Anamesis and physical examination are very important in establishing a diagnosis of anorectal malformations. Plain radiographs of the lumbar spine and sacrum should be taken to evaluate the hemivertebrae and sacruml spine. Generally, low-lying malformations can be corrected directly with Posterior Sagitttal Anorectoplasty (PSARP) or anoplasty, while high-lying malformations require 3 stages of surgery, including the creation of a temporary colostomy. A colostomy is needed for decompression and protection against the possibility of intestinal obstruction.